Analisis Kebijakan Pencegahan dan Penanggulangan Penyakit: Studi Kasus Penanganan Pandemi Covid-19 di Kabupaten Banyumas - Denomika, Adinda Putri (Journal of Politics and Policy, 2023)
Covid-19 is an infectious disease that emerged at the end of December 2019 in Wuhan, China and soon spread rapidly throughout the world, including Indonesia. Covid-19 not only threatens human health and safety, but also has an impact on all sectors, whether economic, social, cultural, educational, and political. With a qualitative case study approach, this paper explains how the policy implementation of the Banyumas Regional Regulation Number 2 of 2020 in handling the Covid-19 pandemic in Banyumas. This paper uses the theory of public policy implementation from Merilee S. Grindle to know how far the Content of Policy and Context of Policy has run as expected by the Banyumas Regional Regulation Number 2 of 2020 in handling the Covid-19 pandemic in Banyumas. The results of the study indicate that the implementation of the Banyumas Regional Regulation policy No. 2 of 2020 in handling the Covid-19 pandemic in Banyumas has not been implemented properly, this was because the indicators in Grindle theory which became the research benchmark had not been fulfilled optimally, the benefits that were not channeled properly, the degree of change that has not been achieved, the location of decision making is not firm, the lack of supporting resources, the implementation of the strategy is not optimal, and the level of compliance and responsiveness of the implementers is minimal.